Examining the Influence of E-WOM, Social Media Marketing, and Subjective Norms on Green Purchase Intention Avoskin Skincare Product in Yogyakarta: A Literature Review - Tiara, Luh Putu; Religia, Yoga (Faculty of Islamic Economics and Business, Madura Islamic State University, 2025)
The increasing awareness of environmental sustainability has driven consumers to adopt eco-friendly products, including green skincare items. Avoskin, a popular skincare brand in Yogyakarta, has attracted attention due to its environmentally conscious initiatives and marketing strategies. This study examines the influence of electronic word-of-mouth (E-WOM), social media marketing, and subjective norms on green purchase intention. By synthesizing previous studies, this literature review explores how digital communication and social influences shape consumer behavior towards purchasing Avoskin skincare products. This research employs a literature review method, synthesizing scholarly articles, research papers, and relevant theories from the past decade. The study focuses on the Theory of Planned Behavior (TPB) to explain the relationship between subjective norms, attitudes, and perceived behavioral control in influencing purchase intentions. Data are sourced from peer-reviewed journals, online databases, and case studies related to green marketing, E-WOM, social media, and consumer behavior. The review highlights that E-WOM plays a critical role in building trust and influencing consumer perceptions of Avoskin's eco-friendly claims. Social media marketing campaigns significantly enhance brand visibility and consumer engagement, promoting green purchase intention. Furthermore, subjective norms, including family, peer influence, and societal expectations, positively impact individual decisions to purchase green products. Combined, these factors create a robust framework for understanding the growing demand for sustainable skincare products like Avoskin in Yogyakarta.